Local cerebral glucose utilisation in chronic alcoholics: a positron tomographic study. Issue 10 (October 1986) - Samson, Y; Baron, J C; Feline, A; Bories, J; Crouzel, C
Abstract : Using positron tomography, a study of regional cerebral glucose utilisation was performed prospectively in a highly selected group of six neurologically unaffected primary chronic alcoholics. In this group, neuropsychological, behavioural and CT scan anomalies were comparable with those previously reported in more extensive studies. With respect to age-matched control values, cerebral metabolic rate was not significantly modified in the selected cortical, subcortical and cerebellar regions of interest. However, the metabolic regional distribution index, which reflects the distribution pattern of glucose utilisation, was selectively and significantly decreased in the medio-frontal area, pointing to a limbic metabolic dysfunction apparently linked to chronic alcoholism.